2010
DOI: 10.1352/1944-7558-115.3.234
|View full text |Cite
|
Sign up to set email alerts
|

Autism Symptom Topography and Maternal Socioemotional Functioning

Abstract: Researchers examining the relationship of autism symptomatology and maternal stress have defined symptomatology in terms of level of severity, frequency of occurrence, or symptom type. In the present study, the relationship of maternal perceptions of these dimensions, along with a fourth, symptom diversity, and negative and positive indices of maternal socioemotional functioning was evaluated. Results indicate that each of these symptom dimensions was correlated with most of the measures of negative socioemoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 33 publications
5
67
1
7
Order By: Relevance
“…Considering that levels parental responsiveness leads quality of parent-child interactions, previous research findings also support that children's severity of autism may have a negative impact on the quality of parent-child interactions (Yoder and Warren, 1998). In addition, present study findings and previous studies (Ekas et al, 2010;Yoder et al, 1998) suggested that children with autism who have severe levels of autism are exposed to low levels of maternal responsivity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Considering that levels parental responsiveness leads quality of parent-child interactions, previous research findings also support that children's severity of autism may have a negative impact on the quality of parent-child interactions (Yoder and Warren, 1998). In addition, present study findings and previous studies (Ekas et al, 2010;Yoder et al, 1998) suggested that children with autism who have severe levels of autism are exposed to low levels of maternal responsivity.…”
Section: Discussionsupporting
confidence: 81%
“…Spiker and colleagues (2002) indicated that mothers of children with autism can have difficulty in developing and maintaining interactions with their children with autism. In relation to the findings obtained from the present study, Ekas and Whitman (2010) suggested that children's autism severity could be associated with parent-child interaction problems. In another study, Wan and colleagues (2011) found that parents of children having high risk of autism exhibited low levels of responsivity during their interactions with their children in comparison to the parents of children having low risk of autism.…”
Section: Discussionsupporting
confidence: 79%
“…Because they often fill the role of primary caregiver, mothers are especially vulnerable to unique types of parenting stress (Ulus et al 2012). To illustrate this point, Ekas and Whitman (2010) found that adolescents with autism spectrum disorder exhibited a more challenging profile of autism spectrum disorder symptoms, cognitive impairments, and co-occurring behavioral problems than younger children with autism spectrum disorder. Parents, especially mothers, of youth and adolescents with autism spectrum disorder, were at particularly high risk for poor psychological well-being as compared to parents of children without disabilities (Ekas and Whitman 2010).…”
Section: Parentsmentioning
confidence: 99%
“…To illustrate this point, Ekas and Whitman (2010) found that adolescents with autism spectrum disorder exhibited a more challenging profile of autism spectrum disorder symptoms, cognitive impairments, and co-occurring behavioral problems than younger children with autism spectrum disorder. Parents, especially mothers, of youth and adolescents with autism spectrum disorder, were at particularly high risk for poor psychological well-being as compared to parents of children without disabilities (Ekas and Whitman 2010). To further underscore this point, Hartley and Schultz (2015) sought to identify which support needs were important to mothers, compared to fathers, of children with autism spectrum disorder.…”
Section: Parentsmentioning
confidence: 99%
“…Dado que la severidad de la sintomatología autista se ha mostrado en numerosas ocasiones como un importante predictor del estrés parental (Ekas y Whitman, 2010;Lyons, Leon, Phelps y Dunleavy, 2010;Pozo y Sarriá, 2014), parecería posible pensar que el efecto aditivo de la sintomatología de TEA y TDAH repercutiría negativamente en los niveles de estrés parental. Sin embargo, los trabajos incluidos en esta revisión no permiten realizar de manera tajante esta afirmación, ya que no se han hallado diferencias en estrés parental (Miranda et al, 2015), ni en calidad de vida familiar en familias de niños con TEA+TDAH y en familias con estos trastornos de manera aislada (Van Steijn et al, 2013.…”
Section: Discussionunclassified